Electrochemical Detection of Sulfadiazine by Sensors based on Chemically Modified Carbon Electrodes: A Review - Ben Brahim, Khalid A.; Bendany, Mohamed; El Hamdouni, Youssra; Abbi, Khaoula; Bakkouche, Chaymae; Fattoumi, Hatim; Hermouche, Lina; Labjar, Najoua; Dalimi, Mohamed; El Hajjaji, Souad (Current Topics in Medicinal Chemistry, 2023)
The consumption of medicines (usually pharmaceuticals and chemical health products) has increased in recent decades due to the demand for medicines for various diseases (headache, relapsing fever, dental absence, streptococcal infection, bronchitis, ear and eye infections). Instead, their overuse can lead to serious environmental damage. Sulfadiazine is one of the most often used antimicrobial medications for both human and veterinary therapy, yet its presence in the environment, even in low quantities, offers a potential concern as an emergency pollutant. It is vital to have a monitoring that's quick, selective, sensitive, stable, reversible, reproducible, and easy to use. Electrochemical techniques realizing cyclic voltammetry (CV), differential pulse voltammetry (DPV), and square wave voltammetry (SWV), using a modified electrode based on carbon as a surface modifier are an excellent option that makes control simple and quick owing to their cheap cost and convenience of use, while also safeguarding human health from drug residue buildup. This study discusses different chemically modified carbon-based electrodes such as graphene paste, screen printed electrode, glassy carbon, and boron diamond doped electrodes for SDZ (sulfadiazine) detection in various formulation feeds, pharmaceuticals, milk, and urine samples, the results obtained also show high sensitivity and selectivity with lower detection limits compared to matrix studies, which may explain its use in trace detection. Furthermore, the effectiveness of the sensors is assessed by other parameters including buffer solution, scan rate, and pH. Also, a method for real sample preparation was also discussed in addition to the different methods mentioned.
Keywords: Sulfadiazine